Design, Synthesis and Cholinesterase Inhibitory Potential of 6H-benzo[c] Chromen-6-one, and 7,8,9,10-tetrahydro-benzo[c] Chromen-6-one Derivatives - Norouzbahari, Maryam (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Alzheimer’s disease (AD) is one of the neurodegenerative diseases of the central nervous system. Although its first diagnosis by Alois Alzheimer goes back to century, its pathophysiology has not been clearly described. Therefore, there is no drug present that totally cures the disease. The main symptom of the disease, disability in cognitive symptoms, has triggered scientists to discover agents aiding in the relief of the decline in the cognition. Today, we have several agents employed in clinic to slow down the progress of the cognitive decline. These drugs are cholinesterase inhibitor molecules and they do not completely cure the disease state, but they are beneficial in the treatment of AD symptoms. The limited number of drugs and the debate on their efficiency as well as the incidence and economic burden of AD create big opportunities to medicinal chemists to design novel drug candidates that might possess better potency and efficacy for the treatment of the AD. From this point of view; we have designed novel urolithin analogs as drug candidates for the treatment of cognitive symptoms of AD within this study. Urolithins are benzo [c] chromen analogues, available as ellagitannin metabolites. Ellagitannins are abundant in berry-fruits and various types of nuts obtained through nutrition. Although these type nutrition have been suggested to relief the symptoms of AD, their main absorbed metabolites within the biological systems, urolithins, are not potent inhibitor of cholinesterase enzymes, the validated targets of AD. Employing the drug-like properties of urolithins we have designed ten novel urolithin analogues promising to be the potent inhibitors of AD. The ten novel urolithin derivative compounds were synthesized with appropriate methodology and their structure identification studies were achieved utilizing modern chromatography and instrumental-spectral techniques. The title compounds synthesized were evaluated in biological experiments. At one hand, their potential to inhibit cholinesterase enzymes was screened. On the other hand, the title compounds were also assayed in the cholinesterase induced amyloid beta aggregation assays. The results indicated that, the title compounds are promising and their potency is comparable to the activity of current drugs, also employed as references in biological assays. In addition to these, the possible interaction of the title compounds with the active site of the cholinesterase enzyme was also investigated employing the molecular docking programs. The results revealed out potential functional groups present within the design crucial for the determination of the pharmacophore system. Keywords: Cholinesterase inhibitor, Amyloid beta aggregation, Urolithin derivatives

ÖZ: Alzheimer hastalığı (AH) merkezi sinir sisteminin nörodejeneratif hastalıklarından biridir. Hastalığın Alois Alzheimer tarafından yapılan ilk tanısı, yüzyıl geriye gitse de, patofizyolojisi hala açık bir şekilde tanımlanmamıştır. Bu nedenle, hastalığı tamamen iyileştiren hiçbir ilaç mevcut değildir. Hastalığın ana semptomu, bilişsel belirtilerdeki eksiklilk, bilim insanlarını, bilişteki gerilemenin hafifletilmesine yardımcı olan yeni bileşikleri keşfetmeye yönlendirmiştir. Bugün, bilişsel gerilemenin ilerlemesini yavaşlatmak için klinikte birkaç ilacımız vardır. Bu ilaçlar kolinesteraz inhibitör molekülleridir ve hastalık durumunu tamamen iyileştirmezler, ancak AH semptomlarının tedavisinde yararlıdırlar. Sınırlı sayıda ilaç ve etkinlikleri ile birlikte AH'in insidansı ve ekonomik yükü konusundaki tartışma, farmasötik kimyacıları AH tedavisinde daha iyi potansiyel ve etkinliğe sahip olabilecek yeni ilaç adayları tasarlamak için büyük fırsatlar yaratmaktadır. Bu açıdan bakıldığında; bu çalışmamızda, AH'nin bilişsel belirtilerinin tedavisinde kullanılabilecek ilaç adayı yeni ürolithin analogları tasarladık Urolithinler, ellagitannin metabolitleri olarak bulunan benzo [c] chromen analoglarıdır. Ellagitanninler çilekli meyveler ve kuruyemişlerde bol miktarda bulunmaktadır. Bu tip beslenme, AH semptomlarını hafifletmek için önerilmiş olsa da, biyolojik sistemlerdeki ana emilen metabolitleri olan ürolithinler, AH'in onaylanmış hedefleri olan kolinesteraz enzimlerinin potent inhibitörü değildir. Ürolithinlerin ilaç- olabilme özelliklerini kullanarak, AH'in güçlü inhibitörleri olacağına inandığımız on yeni ürolitin analoğu tasarladık. On yeni ürolitin türevi bileşik, uygun metodoloji ile sentezlendi ve yapı tanımlama çalışmaları, modern kromatografi ve enstrümantal spektral teknikler kullanılarak gerçekleştirildi. Sentezlenen orijinal bileşikler biyolojik deneylerde değerlendirildi. Bir taraftan, kolinesteraz enzimlerini inhibe etme potansiyeli tarandı. Öte yandan, orijinal bileşikleri aynı zamanda kolinesteraz ile indüklenen amiloid beta agregasyon deneylerinde aktiviteleri incelendi. Sonuçlar, bileşiklerin aktivitelerinin umut verici olduğunu ve potensiyellerinin, biyolojik çalışmalarda kullanılan referans ilaçların aktivitesiyle karşılaştırılabilir olduğunu gösterdi. Buna ek olarak, bileşikler ile kolinesteraz enziminin aktif bölgesi arasındaki olası etkileşim, moleküler yerleştirme programları kullanılarak araştırılmıştır. Sonuçlar, tasarım için kullanılan farmakofor sistemde gerekli olan önemli fonksiyonel grupları ortaya koymuştur. Anahtar Kelimeler: Kolinesteraz inhibitörü, Amiloid beta agregasyonu, Urolithin türevleri.
Doctor of Philosophy in Chemistry. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2018. Co-Supervisor: Assoc. Prof. Dr. Mustafa Gazi, Supervisor: Assoc. Prof. Dr. Hayrettin Ozan Gülcan.
Keywords: Chemistry; Cholinesterase inhibitor; Amyloid beta aggregation; Urolithin derivatives